2006
DOI: 10.1111/j.1572-0241.2006.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Endoscopic Ultrasonographic Evaluation of the Frequency of Nonfunctioning Pancreaticoduodenal Endocrine Tumors in Patients with Multiple Endocrine Neoplasia Type 1

Abstract: The frequency of nonfunctioning pancreatic endocrine tumors is higher (54.9%) than previously thought. The size and number of these tumors can increase over time. Pancreatic EUS should be performed once MEN1 is diagnosed to monitor disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
115
0
12

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(129 citation statements)
references
References 34 publications
2
115
0
12
Order By: Relevance
“…EUS as a harmless procedure improves non-surgical pancreatic imaging and enables to detect and localize symptomatic neuroendocrine pancreatic tumours better and earlier and may be helpful in planning therapeutical strategy (Bansal et al 1999, Kann et al 2001, 2003, 2006, Wamsteker et al 2003, Hellman et al 2005, McLean & Fairclough 2005, Thomas-Marques et al 2006. It also has been introduced into the diagnostic repertoire in MEN1-disease, however also raising new and specific questions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EUS as a harmless procedure improves non-surgical pancreatic imaging and enables to detect and localize symptomatic neuroendocrine pancreatic tumours better and earlier and may be helpful in planning therapeutical strategy (Bansal et al 1999, Kann et al 2001, 2003, 2006, Wamsteker et al 2003, Hellman et al 2005, McLean & Fairclough 2005, Thomas-Marques et al 2006. It also has been introduced into the diagnostic repertoire in MEN1-disease, however also raising new and specific questions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, EUS enables to visualize small neuroendocrine tumours down to a diameter of 1-2 mm can be visualized (Kann et al 2001, 2003, Wamsteker et al 2003, Hellman et al 2005, Thomas-Marques et al 2006. Therefore, its use in endocrinology for imaging of the endocrine pancreas and also the adrenal glands is becoming more frequent (Kann et al 1998a, 1998b, 1999, 2004, Kann 2005.…”
Section: Introductionmentioning
confidence: 99%
“…The gold standard modalities for pancreatic gland analysis in patients with MEN1 are EUS and MRI, which are complementary (Barbe et al 2012). Although the sensitivity of EUS is much higher than that of MRI for the detection of pNETs (Thomas-Marques et al 2006, Barbe et al 2012, Kappelle et al 2017, larger tumors (>2 cm) can be found using MRI, especially in the pancreatic tail (Barbe et al 2012). Liver MRI is the reference imaging modality for the detection of liver metastases (d 'Assignies et al 2013).…”
Section: Tumor Localizationmentioning
confidence: 99%
“…A recent prospective study showed that the rate of NFPETs in MEN1 patients is higher than 55% when endoscopic ultrasound (EUS) is performed to detect them [7]. Since the number and size of the NFPETs tend to increase in time and the affected population is relatively young (median age is 39 years), this rate is certainly going to grow as time passes by.…”
Section: Discussionmentioning
confidence: 99%
“…The revision of the NFPETs in MEN1 has clearly shown an association between large primary tumor size, the presence of distant metastases and the mortality due to tumoral progression [7][8][9]. EPTs have been recently stratified, on the basis of the WHO classification, in 3 categories: benign tumors, well-differentiated carcinomas with low-grade malignant behaviour and poorly-differentiated carcinomas with high grade malignant behaviour [10].…”
Section: Discussionmentioning
confidence: 99%